Prevalence and determinants of obesity and overweight among school children of Ahmedabad City, Gujarat: a cross sectional study - Thaddanee, Rekha; Chaudhari, Upendra Rameshbhai; Thakor, Nilesh (International Journal of Contemporary Pediatrics, 2016)
Background: Childhood obesity itself is a predictor of adult obesity and of higher than expected adult morbidity and mortality. Due to difficulty in the treatment of obesity in adults and the many long-term adverse effects of childhood obesity, prevention of childhood obesity has now been recognized as a public health priority. The objective of the study was to know the prevalence and determinants of obesity in school children of Ahmedabad city. Methods: The present cross sectional study was undertaken during September 2015 to December 2015 in randomly selected 10 schools of Ahmedabad city, Gujarat by Department of Pediatrics and Community Medicine of GMERS Medical College, Dharpur-Patan, Gujarat, India. Total 2562 children between the age group of 10 to 15 years were examined after taking written informed consent of their parents using pre-designed, pre-tested, semi-structured proforma. Anthropometric measurements were taken and BMI were calculated. The prevalence of overweight and obesity were determined based on the IOTF (International Obesity Task Force) criteria. Various determinants of obesity and overweight were studied by interviewing children. Thus collected data was analyzed using SPSS 17 (Trial version). Results: Out of 2562 children males were 54.09% and females were 45.9%. Prevalence of obesity and overweight was 5.62% and 9.99% respectively. Overall prevalence of obesity was more among female population (6.8%) as compared to that in males (4.62%). The prevalence of obesity was found to be highest among 15 years age group (8.22%). The prevalence of obesity and overweight was significantly higher amongst less active group (9.3 % and 13.95%, respectively) as compared to more active group. Prevalence of obesity and overweight was significantly higher in the group of children who spent >2 hours daily in front of television or computers. The prevalence of obesity and overweight was significantly higher amongst group of children who took daily calories above RDA (18.57% and 15.19% respectively) as compared to the other group. The prevalence of obesity and overweight was significantly higher in them (8.91% and 13.36%) as compared to those who took junk food less than or equal to 2 times per week (1.71% and 5.98% respectively). The prevalence of obesity and overweight among children having parents with history of obesity was 46.15% and 17.94%, respectively which was significantly higher than those without parental history of obesity (4.34% and 9.74%). Conclusions: High prevalence of obesity and overweight in school children indicate an urgent need to increase awareness via education and motivation of all stakeholders.